Melioidosis: A Neglected Infection in Bangladesh - Chowdhury, Fazle Rabbi; Roy, Chandan Kumar; Barai, Lovely; Paul, Shrebash; Chowdhury, Forhad Uddin Hasan; Mazumder, Sraboni; Farook, Saika; Jilani, MSA (Journal of Medicine, 2021)
Bangladesh is an example of a highly populous, agricultural country where melioidosis may be a significantly under diagnosed cause of infection and death. A recent regression model predicted 16,931 cases annually in Bangladesh with a mortality rate of 56%. However, we only manage to confirm (culture) around 80 cases in last 60 years. A lack of awareness among microbiologists and clinicians and a lack of diagnostic microbiology infrastructure are factors that are likely to lead to the underreporting of melioidosis. Melioidosis transmits through inoculation, inhalation and ingestion. Diabetes mellitus is the most common risk factor (12 times higher chance of getting the infection) predisposing individuals to melioidosis and is present in >50% of all patients. The clinical presentation is widely varied and can be mistaken for other diseases such as tuberculosis or more common forms of pneumonia giving rise to its nickname as the “great mimicker”. Disease manifestations vary from pneumonia or localized abscess to acute septicemias, or may present as a chronic infection. Culture is considered the current gold-standard for diagnosis and culture-confirmation should always be sought in patients where disease is suspected. It is strongly recommended that any non–Pseudomonas aeruginosa, oxidase-positive, Gram-negative bacillus isolated from any clinical specimen from a patient in an endemic area should be suspected to be Burkholderia pseudomallei (BP). In addition, based on antibiogram, any Gramnegative bacilli that are oxidase-positive, typically resistant to aminoglycosides (e.g., gentamicin), colistin, and polymyxin but sensitive to amoxicillin/clavulanic acid should be considered as BP. This bacteria is inherently resistant to penicillin, ampicillin, first generation and second-generation cephalosporins, gentamicin, tobramycin, streptomycin, and polymyxin. For intensive phase (10 to 14 days), ceftazidime or carbapenem is the drug of choice. For eradication phase (3 to 6 months), oral trimethoprim/ sulfamethoxazole is the drug of choice. Surgery (drainage of abscess) has an important role in the management of melioidosis. Preventive measures through protective gears could be useful particularly for the risk groups. J MEDICINE 2021; 22: 139-145